Narrativas de formação : (re)trilhando experiências do estágio supervisionado em Letras-Inglês - Fadini, Valéria Septímio Alves (2013)
This work aims to understand how student teachers of the English Language and Literature undergraduate program at Universidade Federal do Espírito Santo (Ufes) make use of the experiences in Teaching Practicum II to construct their own identity as teachers. We assume that Teaching Practicum is essential for the process of pre-service teacher education, once it is the moment student teachers learn the profession by having the opportunity to know the working place, connect theory to practice, develop professional identity, produce knowledge based on teaching and research on pedagogical practice, in few words, try what it means to be a teacher under the guidance of experienced teachers, in a collaborative perspective between the university and field schools. The theoretical reference of this research is based on Pimenta and Lima (2004) studies on Teaching Practicum, on Nóvoa (2010, 2000); Josso (2010, 2008, 2004) and Souza (2008, 2006) work on the use of educational narratives, in the (auto)biographical methodology. Therefore, it is a qualitative research, which analyses the educational narratives in five out of nine final teaching practicum reports, as well as in online questionnaires, produced by nine out of 22 students of the mentioned subject, in the first semester of 2011. In order to broaden our comprehension of the pre-service teacher education process, we included Teaching Practicum retrospective narratives produced by both the Teaching Practicum supervisor and the experienced school teacher whose classes were observed during teacher training period. The results show that collaborative work is essential for the students’ good teaching performance during the practical program and that Teaching Practicum experiences contribute to build up necessary teaching skills and knowledge and an inquiry posture in the pre-service teachers. To sum up, one can say that the reflective and research experiences developed during Teaching Practicum significantly contributed to students’ education, encouraging commitment to the complex educational reality in which they are placed, and, reinforcing their awareness of the necessity of long-life education